Bibliometric analysis of mobile learning user experience industrial revolution 5.0 - Ariffin, Shamsul Arrieya; Kamsin, Amirrudin; Mustapha, Ramlan (Institute of Advanced Engineering and Science, 2024)
User experience or usability is under research, particularly in mobile learning in the era of industrial revolution (IR) 5.0. This article discusses incorporating sophisticated mobile technologies such as augmented reality (AR), virtual reality (VR), and artificial intelligence (AI) into the user experience in educational settings. Therefore, this paper investigates the relatively new revolutionary potential of mobile learning user experience in the context of the IR 5.0, where the digital and technology spheres meet for better user experiences, particularly for students in learning. The research explores novel meta-mobile technology approaches by examining concrete cases from 2012, analyzing their impact, and improving the user experience. Likewise, this article elucidates the need for mobile learning user experience research based on bibliometric analysis.